استخدام المرشحات ثنائية الطبقة في تنقية مياه الشرب في السن - أحمد قصير; هناء سلمان; سماح أسعد (Tishreen University, 2019)
يتلخص موضوع هذا البحث في دراسة فعالية تنقية مياه نبع السن من المواد العالقة بطريقة الترشيح السريع باستخدام المرشحات السريعة ثنائية الطبقة (رمل- انتراسيت) ولذلك تم تصميم نموذج لمحطة مخبريه تتألف من مرشح ثنائي الطبقة ارتفاع الحشوة الكلي (1m) تتألف من (60cm) رمل ومن (40cm) انتراسيت, وباتجاه جريان من الأعلى إلى الأسفل وبسرعات متفاوتة, أجريت مجموعتان من التجارب على هذا المرشح الأولى كانت بدون إضافة مخثر والثانية كانت مع إضافة مخثر حيث تراوحت قيم سرعة الترشيح بين m/h(7-16) وقيم العكارة بين g/m³(7-28) وبعد مقارنة النتائج بين الحالتين تبين أنه باستخدام المرشحات السريعة ثنائية الطبقة (رمل- انتراسيت) مع إضافة مخثرات يمكن تنقية المياه السطحية الحاوية على مواد عالقة تصل حتى 30 g/m³ بكفاءة جيدة كذلك تخفيض كمية مياه الغسل والحصول على درجة تنقية أعلى وإنتاج كمية مياه أكبر كذلك التوفير المادي. This research aims to study the filtration efficiency of Al-Sinn water by removing suspended solids using two-layer rapid filtration (sand-anthracite), To achieve that, a filtration system consisting of a two-tier filter has been designed; its entire height is (1m) consisting of two layers: the first one is (60cm of sand) and the second one (40cm of anthracite), with water flowing downwards at different filtration speeds; the filtration speed was (7-16) m/h, and turbidity was (7-28)g/m³. Two kinds of experiment have been carried out with and without using coagulants. After comparing the results of both cases, it turned out that by using two-tier speed coagulant surface water containing suspended solids of up to (30 g/m³ can be treated more efficiently, and could reduce the amount of washing water and achieve a higher degree of filtration and produce more water at a low cost.